Google Site as a Learning Media in the 21st Century on the Protists Consept - Dieny Aulia; Kaspul Kaspul; Maulana Khalid Riefani (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2021)
The development research was carried out using the 4D development model adapted from Thiagarajan. This research and development aims to create and develop learning media that can support the learning process. The website-based learning media for the Protista concept for tenth grade Biology High School is carried out because of the importance of technology-based media innovation in 21st-century learning. The learning media developed is a website using google site equipped with a combination of text, images, animation, audio, video, and a simply designed navigation bar. The research and development of this website-based learning media uses a 4D development model (Define, Design, Develop, and Disseminate), but this research is focused on the responses of students in using the google sites learning media. The results of student responses to the learning media website "DIEYA PROTISTA'' are classified as very good with an average response score of 4.50. This response shows that the learning media that was developed theoretically and procedurally has been suitable for use in teaching Protists in tenth grade. AbstrakPenelitian pengembangan yang dilakukan menggunakan model pengembangan 4D yang diadaptasi dari Thiagarajan. Penelitian dan pengembangan ini bertujuan untuk membuat dan mengembangkan media pembelajaran yang dapat mendukung proses pembelajaran. Media pembelajaran berbasis website pada konsep Protista untuk SMA Kelas X Biologi ini dilakukan karena pentingnya inovasi media pembelajaran berbasis teknologi di pembelajaran abad 21. Media pembelajaran yang dikembangkan ialah google sites dilengkapi dengan penggabungan teks, gambar, animasi, audio, video dan menu navigasi yang didesain sederhana. Penelitian dan pengembangan media pembelajaran berbasis website ini menggunakan model pengembangan 4D (Define, Design, Develop, dan Disseminate), namun penelitian ini difokuskan pada respon peserta didik dalam menggunakan media pembelajaran google sites. Hasil respon peserta didik terhadap media pembelajaran website “DIEYA PROTISTA” tergolong sangat baik dengan rerata skor respon 4,50. Respon ini menunjukkan media pembelajaran yang dikembangakan secara teoritis dan prosedural telah layak digunakan pada pembelajaran Protista di kelas X.